The Influence of Financial Technology on The Financial Performance of Islamic Banking in Indonesia - prihastuti, asepma hygi; Meteab Mubarak, Bazyad Abdullah (Journal of Islamic Financial Technology, 2023)
This study aims to determine the influence of fintech on the financial performance of Islamic banking in Indonesia. This research is quantitative research using secondary data. The data analysis techniques used are descriptive analysis, normality test, panel data model selection through common effect, fixed effect, random effect, panel data model including Chowtest, Hausman test, classical assumption test including multicollinearity, hypothesis autocorrelation test including t-test, coefficient of determination (R2) test, and simple linear regression analysis. The results showed that there is a partial influence of fintech on the financial performance of Islamic banking in Indonesia (ROA). The more the development of fintech services in Islamic banking in Indonesia, the more significant the influence on the performance of Islamic banking in Indonesia (ROA).